Origin of Lake Singkarak in the Padang Highlands (Central Sumatra) - M.T. Zen (Institute for Research and Community Services (LPPM) ITB, 1970)
Since long it has been accepted that Lake Singkarak in the Padang Highlands is nothing else but a remnant of a gigantic volcano-the Singkarak volcano- which one blew off its top to form a lake. Van Bemmelen though not referring to Singkarak Lake especially, explained the numerous depressions in Sumatra as the combined result of volcanic and tectonic activities, a phenomenon he called volcano-tectonic process which caused the formation of the so called volcano-tectonic depressions.A short visit to the lake area in the months of February and March (1970) convinced the author that the Singkarak Lake is neither a volcanic ruin nor a volcano-tectonic depression in the sense of Van Bemmelen.Faulting evidences, morphology and the position of the Singkarak trough plus the distribution of volcanic products north and south of the lake lead to the conclusion that the Singkarak trough is a depression making part of the 1650 km graben zone which stretches from Sumatra's northern tip until the Semangko valley in the SE. Field evidences suggest that the lake results from a damming process by volcanic material produced by the Marapi-Singgalang-Tandikat volcanoes in the north and by the products from the Talang volcano in the south.